Rukhṣah bagi Pasien Kemoterapi: Analisis Maqasid al-Shariʿah tentang Pelestarian Diri, Martabat dan Fatwa Kontemporer - Mutammimah, Mutammimah; Nurhaqiqiy, Annisa Taqiyya; Kartika, Khofifah Ayu; Muhayar, Marhadi (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2026)
Chemotherapy, as a major therapeutic modality for cancer, frequently causes hair discoloration and alopecia, affecting approximately 60–65% of patients. Beyond physical consequences, these conditions often result in psychological distress, diminished self-esteem, social withdrawal, and even refusal to continue life-saving treatment. Contemporary Islamic legal opinions, particularly the Indonesian Council of Ulama (MUI) Fatwa No. 23 of 2012 concerning hair dye, have not specifically addressed this medical context, creating a normative gap (farāgh tashrī‘ī). This study examines the permissibility of applying rukhṣah (legal concession) for chemotherapy patients to dye their hair within the framework of Maqāṣid al-Sharīʿah. This study employed normative legal research based on library sources, utilizing a maqāṣid-oriented approach. Primary and secondary legal materials, including classical juristic opinions, contemporary fatwas, and medical literature on chemotherapy, were analyzed qualitatively through doctrinal and maqāṣidic analysis. The findings reveal that hair alterations resulting from chemotherapy constitute pathological conditions beyond the patient's volition. The effective cause (‘illah) underlying the prohibition of black hair dye, namely deception (khidā‘) concerning age or appearance, is absent in this context. Furthermore, the legal construction of rukhṣah can be established upon four principles: psychological self-preservation (ḥifẓ al-nafs), preservation of human dignity (ḥifẓ al-‘irḍ), elimination of hardship (raf‘ al-ḥaraj), and maṣlaḥah mursalah. The study concludes that chemotherapy patients may be granted a rukhṣah to dye their hair as a means of preserving psychological well-being and human dignity. Contemporary fatwas should therefore incorporate specific provisions addressing medical conditions experienced by patients. The novelty of this study lies in reconstructing the jurisprudential basis for hair dye permissibility through the integration of medical realities and Maqāṣid al-Sharīʿah.